Pemberdayaan RT 041 Liliba dalam Pengelolaan Sampah Berkelanjutan dan Pemasaran Produk Ramah Lingkungan - Lopes Amaral, Maria Augustin; Manehat, Beatrix Yunarti; Tukan, Gerardus Diri; Boelan, Erly Grizca; An, Clarisa Margareth; Gani, Elisabeth Adelia Merdekawati; Setiawan, Apolinaris; Gokok, Gaspar Antonius Padua Rapok; Bria, Kristina; Boikh, Ananda Oky Mekel M.; Luan, Olyva Renyarosari (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
The improper waste management in RT 041 Liliba, Kupang City, has become an urgent environmental issue. Organic and inorganic waste are often discarded without proper segregation, contributing to air and soil pollution. To address this, a training and mentoring program was implemented focusing on waste segregation, managing plastic waste through the Waste Bank, and processing food waste into liquid fertilizer and compost. The program involved 30 participants, including RT administrators and local residents. The results showed an improvement in community awareness and knowledge about waste segregation and management, as well as increased participation in the Waste Bank program and fertilizer production. It is hoped that this initiative can be continued and expanded to other communities in Kupang City to create a cleaner and healthier environment. The success of this program highlights the importance of collaboration between the community, RT administrators, and other stakeholders in managing waste responsibly and sustainably.